A Study of RMB Internationalization Path Based on Border Area Perspective. (29th October 2019) - Ko, Po Sheng; Wu, Cheng Chung; Mai, Ying Shih; Xu, Zhongrong
Abstract : At present, the enhancement of China's comprehensive national strength, stable currency policy, and the new round of opening-up strategy layout have provided opportunities for the financial development in border areas, especially for the RMB internationalization advancement in border areas, while the lagging financial system construction in current border areas also challenges its RMB internationalization. Based on Friedman's monetary demand theory (1970), the thesis has combined the periodical characteristics and selected the representative Yunnan province in the border areas as the object, taking into overall consideration the two paths of geography and function for RMB internationalization in border areas, so as to build the two-dimensional path theory framework of RMB internationalization from a border area perspective. In view of the above, a panel econometric regression model is built to estimate the factors influencing RMB internationalization path in Yunnan province. The results show that the process of opening up to the outside world in Yunnan province is its major driving force for RMB internationalization, while the great fluctuation of price level tends to hinder the process advancement and such possible impact of overall revenue on RMB internationalization development as the reginal disparity.